Five little monkeys reading in bed - Christelow, Eileen (Boston : Clarion Books, 2011)
The Five Little Monkeys cannot resist reading, even after Mama tells them it is time for bed.
Kirkus Review, July 2011.
Kirkus Review.
1.7
K-3
AD490L
Accelerated Reader AR
Keywords: Books and reading -- Juvenile fiction; Bedtime -- Juvenile fiction; Monkeys -- Juvenile fiction; Mother and child -- Juvenile fiction; Human behavior -- Juvenile fiction; Books and reading -- Fiction; Bedtime -- Fiction; Monkeys -- Fiction; Mother and child -- Fiction; Behavior -- Fiction; Books and reading -- Fiction; Bedtime -- Fiction; Monkeys -- Fiction; Mother-child relationship -- Fiction; Human behavior -- Fiction